Chapter 7. Growing cities, changing demands: Scope of urban agriculture as a sustainable agricultural intensification strategy in India - Aravindakshan, Sreejith; Hage Aku; Michi Tani (CRC Press, 2024)
The widespread health concerns over chemical-intensive agriculture and recent disruptions of pandemic-induced agricultural supply chains alongside impaired public food distribution systems in urban and peri-urban areas of developing countries have all provided opportunities for the proliferation of urban agriculture (UA) in cities. Urban dwellers are learning to adapt, improvise, and adopt new ways of cultivating vegetables and fruits for home consumption. For example, in Indian cities, the pandemic and associated lockdown have mushroomed several innovations in rooftop cultivation, vegetable kitchen gardens, polyhouse cultivation, and vertical farming. However, UA in cities has provided questionable environmental gains and has not significantly improved urban food security, especially among the poorer sections. Looking at the rapid proliferation of urban farmscapes, one would wonder if this were a sustainable intensification strategy or a temporary bubble. It is hypothesized that several underlying environmental, economic, social, cultural, and political factors induce UA’s emergence, sustenance, and sustainability. Employing a mixed-method approach, this chapter draws on primary data collected from urban farming households in Kerala and Arunachal Pradesh in India, supplemented by secondary data from the national statistical organization and literature reviews. The aim is to delineate the approaches and indicators of UA driving sustainable intensification.